An Evaluation Upon Utilizing Children's Literature: Techniques of Teaching Reading: Enhancing Critical Reading Skills through Children's Literature (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The purpose of this paper was to develop a thematic unit of children'sliterature that combines skills-based and meaning-based reading instruction.The curriculum guide was designed for use with third and fourth graders.Lessons concentrated on relating each story to previously read stories throughguided questioning. Emphasis was placed on critical reading and thinkingskills, as well as the integrating of reading, writing, listening, andspeaking. Furthermore, the researcher concluded that the curriculum effectivelyintegrated the four language art components in meaning-centered readingexperiences which, in turn, enabled children to read, write, listen, and speakmore often and at a higher level.